2017
DOI: 10.3390/ijerph14111405
|View full text |Cite
|
Sign up to set email alerts
|

Placement Stability, Cumulative Time in Care, and Permanency: Using Administrative Data from CPS to Track Placement Trajectories

Abstract: Objectives: The Quebec Youth Protection Act was amended in 2007. The main goal of this reform was to improve placement stability for children who are removed from their home for their protection. Among several legal provisions introduced was the establishment of maximum age-specific durations of out-of-home care, after which a plan must be established to provide stability for children placed in substitute care by finding permanent homes for them. The purpose of this study is (1) to examine trends in placement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The first concerned past experiences in foster care. Research has shown that youth admitted to foster care can experience very different care pathways depending on age at admission, duration of care, and the number of placement moves and breakdowns (see, e.g., Hélie et al, 2017). Three placement trajectories in particular were identified in the original cohort sample using cluster analysis (Hébert & Lanctôt, 2016).…”
Section: Participantsmentioning
confidence: 99%
“…The first concerned past experiences in foster care. Research has shown that youth admitted to foster care can experience very different care pathways depending on age at admission, duration of care, and the number of placement moves and breakdowns (see, e.g., Hélie et al, 2017). Three placement trajectories in particular were identified in the original cohort sample using cluster analysis (Hébert & Lanctôt, 2016).…”
Section: Participantsmentioning
confidence: 99%